End-to-end deep learning pipeline for breast cancer detection, segmentation and classification in contrast-enhanced spectral mammography - Catarino, Jéssica Andreia Pinela (2022)
Tese de Mestrado, Bioinformática e Biologia Computacional, 2022, Universidade de Lisboa, Faculdade de Ciências